Statins and Male Sexual Health: A Retrospective Cohort Analysis. (25th November 2014) - Davis, Richard; Reveles, Kelly R.; Ali, Sayed K.; Mortensen, Eric M.; Frei, Christopher R.; Mansi, Ishak
Abstract Introduction Conflicting reports exist regarding the role of statins in male gonadal and sexual function. Some studies report a beneficial effect, particularly for erectile dysfunction (ED), through statins' anti‐inflammatory and cardiovascular protective properties. Others suggest that statins might be associated with sexual dysfunction through negative effects on hormone levels. Aim This study aims to compare the risk of gonadal or sexual dysfunction in statin users vs. nonusers in a single‐payer healthcare system. Methods This was a retrospective cohort study of all male patients (30–85 years) enrolled in the Tricare San Antonio market. Using 79 baseline characteristics, we created a propensity score‐matched cohort of statin users and nonusers. The study duration was divided into a baseline period (October 1, 2003 to September 30, 2005) to describe patient baseline characteristics, and a follow‐up period (October 1, 2005 to March 1, 2012) to determine patient outcomes. Statin users were defined as those prescribed a statin for ≥3 months between October 1, 2004 and September 30, 2005. Main Outcome Measures Outcomes were identified as the occurrence of benign prostatic hypertrophy (BPH), ED, infertility, testicular dysfunction, or psychosexual dysfunction during the follow‐up period as identified by inpatient or outpatient International Classification of Diseases, 9th Revision, Clinical Modification codes. Logistic regression was used to determine the association of statin use with patient outcomes. Results Of 20, 731 patients who met study criteria, we propensity score‐matched 3, 302 statin users with 3, 302 nonusers. Statin use in men was not significantly associated with an increased or decreased risk of BPH (odds ratio [OR] 1.08; 95% confidence interval [CI] 0.97–1.19), ED (OR 1.01; 95% CI 0.90–1.13), infertility (OR 1.22; 95% CI 0.66–2.29), testicular dysfunction (OR 0.91; 95% CI 0.73–1.14), or psychosexual dysfunction (OR 1.03; 95% CI 0.94–1.14). Conclusions Statin use was not associated with increased risk of being diagnosed with gonadal or sexual dysfunction in men. Further studies using a larger sample may be needed. Davis R, Reveles KR, Ali SK, Mortensen EM, Frei CR, and Mansi I. Statins and male sexual health: A retrospective cohort analysis. J Sex Med 2015;12:158–167.